1998
DOI: 10.1038/sj.onc.1202057
|View full text |Cite
|
Sign up to set email alerts
|

An anchorage-dependent signal distinct from p42/44 MAP kinase activation is required for cell cycle progression

Abstract: Most normal cells require both mitogens and integrinmediated attachment for growth. It is generally accepted that the p42/p44 MAP kinase module, which can be activated by both growth factors and adhesion, plays a critical role in G0 to S phase progression of quiescent cells. Studies on various cultured ®broblasts have shown that removal of anchorage leads to cell cycle arrest in G1 and it has been proposed that adhesion-dependent G1 progression requires the joint regulation of p42/p44 MAP kinase by integrins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
2

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 25 publications
3
38
2
Order By: Relevance
“…1). It is known that the ability of mitogens to activate ERK is anchorage dependent and that loss of responsiveness is complete by 12 h (Le Gall et al, 1998). However, in the case of Akt activation, we found that loss of serum or insulin responsiveness occurs immediately following anchorage removal.…”
Section: Activation Of Akt Is Strictly Adhesion Dependent In Ccl39 Cellscontrasting
confidence: 48%
See 1 more Smart Citation
“…1). It is known that the ability of mitogens to activate ERK is anchorage dependent and that loss of responsiveness is complete by 12 h (Le Gall et al, 1998). However, in the case of Akt activation, we found that loss of serum or insulin responsiveness occurs immediately following anchorage removal.…”
Section: Activation Of Akt Is Strictly Adhesion Dependent In Ccl39 Cellscontrasting
confidence: 48%
“…Following centrifugation, cells were resuspended in serum-free DMEM containing 1% bovine serum albumin (BSA) at 10 5 cells per ml and transferred to spinner flasks, as previously described (Le Gall et al, 1998).…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%
“…These results, combined with the results using U0126, suggest that while MEK may be important for cyclin D1 expression on permissive substrates, it is not sufficient to induce cyclin D1 on polymerized collagen. Evidence showing that activation of ERK in suspended CCL9 cells fails to activate cyclin D1 expression have suggested that other adhesion-dependent signals in addition to ERK may be required in some cell types to induce cyclin D1 (66). One potential mechanism by which ERK is prevented from signaling to cyclin D1 on collagen gel, suggested by the vastly different cell shapes on these substrates, might be cytoskeletal differences between cells adherent to collagen film or collagen gels and the ability to form intracellular cytoskeletal scaffolds important for interaction between signaling proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of p42/p44MAPK, 9 ± 12 or p60 src pathways 13 induce cyclin D 1 expression in a cell adhesion dependent fashion. 14 Integrins are heterodimeric cell surface receptors that mediate cell adhesion to the extracellular matrix (ECM) and transduce biochemical signals, including activation of focal adhesion kinase (FAK). 15 ± 19 Neutralizing antibodies against integrins induce cell detachment followed by apoptosis in epithelial cells.…”
Section: Introductionmentioning
confidence: 99%